PEMANFAATAN RAINWATER HARVESTING UNTUK KEBUTUHAN AIR BERSIH DI PERUMAHAN JAKARTA BARAT - Fakhruddin, Faris; Asriningsih Pranoto, Wati (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
ABSTRACT Jakarta is currently facing a severe clean water crisis, driven by rapid urban population growth and limited availability of freshwater resources. One promising alternative to alleviate this issue is the utilization of rainwater harvesting systems, which can supplement daily water needs, particularly in residential areas. This study evaluates the potential of implementing rainwater harvesting in the Casa Jardin residential complex, with a focus on public facilities such as the Clubhouse, the Marketing Gallery office, and the SOHO commercial units. A quantitative approach was employed, utilizing direct field observations and secondary data including daily rainfall records over a 10-year period. The analysis estimated that an average of 48.51 m³ of rainwater could be collected daily. Based on PAM JAYA’s official water tariffs, this translates into potential monthly savings of approximately IDR 11,607,138.92. Efficiency analysis revealed that the highest efficiency occurred in the SOHO units (over 100%), followed by the Marketing Gallery (19%) and the Clubhouse (7%). However, full efficiency at the SOHO units could not be accurately measured due to many units remaining unoccupied. The findings highlight the financial and environmental benefits of rainwater harvesting, especially in urban settings. ABSTRAK Krisis air bersih menjadi masalah serius di Jakarta akibat peningkatan populasi dan keterbatasan ketersediaan sumber air. Salah satu solusi alternatif yang dapat diterapkan adalah pemanfaatan rainwater harvesting atau pemanenan air hujan untuk memenuhi kebutuhan air. Penelitian ini bertujuan untuk mengkaji potensi pemanenan air hujan di kawasan Perumahan Casa Jardin khususnya pada fasilitas umum Clubhouse Kantor Marketing Gallery, dan Ruko SOHO. Fokus penelitian meliputi pengukuran curah hujan harian, manfaat rainwater harvesting, serta volume air hujan yang dapat ditampung. Penelitian ini menggunakan metode kuantitatif dengan teknik pengumpulan data melalui observasi langsung di lapangan. Berdasarkan penelitian Putra & Pranoto (2019) rainwater harvesting dapat menghemat air sebanyak 87,12% pada hari hujan. Hasil penelitian pada kawasan Casa Jardin di Marketing Gallery, Clubhouse, dan Ruko SOHO didapatkan sebesar 48,51 m3/hari berdasarkan rata-rata curah hujan harian. Efisiensi tertinggi pada pemakaian air hujan dengan air pam untuk Marketing Gallery ± 19% dan Clubhouse 7%. Efisiensi pada Ruko SOHO belum dapat dihitung karena belum terisi penuh seluruh ruko sehingga pemakaian masih relatif dikit sekali.